Community banking strategies : steady growth, safe portfolio management, and lasting client relationships - Boberski, Vincent (Bloomberg Professional., 2010)
Praise for Community Banking Strategies. "In Community Banking Strategies, Vince Boberski not only gives unique and penetrating insights into the triggering events that caused the 'Great Recession' of 2008-2010, but also outlines effective and powerful forward-thinking strategies for community bankers to adopt as they cope with the new financial and market realities that lie ahead. This book is a must-read for any community banker wanting to take advantage of a generational shift in the financial markets and position the bank to thrive in future years."--Camden R. Fine, President and